The Effect of Coaching Practices on Psychological Contract Fulfillment of Student-Athletes - Rezania Davar; Gurney Robert (Sciendo, 2016)
We examine the relationships between coaching practices, psychological contract fulfillment and the impact it has on satisfaction and in-role behavior of student-athletes. We surveyed a total of 183 student-athletes in Canada. Utilizing Partial Least Squares path modeling algorithm, the results confirm that the extent of psychological contract fulfillment is positively related to satisfaction and role-behavior. In addition, practices of compensation, information sharing, and security (i.e. ensuring continuation of position on the team) are related to fulfillment of psychological contracts. However, the data does not provide support for the idea that training is related to the fulfillment of psychological contracts. The results suggest that universities can manage students-athletes' expectations by institutionalizing coaching practices that signal commitments for compensation, information sharing, and provide assurance of position on the team. Such practices have potential to improve the athlete's performance.